Health risk assessment of polycyclic aromatic hydrocarbons (PAHs) in the soil around thermal power plants in southwest China. Issue 7 (28th July 2021) - Zou, Yiping; Liu, Jialin; Liu, Xingchen; Jia, Jianli
Abstract: This study aimed to evaluate the PAH contamination levels and to assess the health risk of PAH in soils of two typical thermal power plants. The PAH content was detected using gas chromatography-mass spectrometry (GC-MS). The carcinogenic risk and the hazard quotient were assessed for health risk using the "Chinese Technical Guidelines for Risk Assessment of Contaminated Sites HJ 25.3-2014." The results showed that the average concentration of Σ16 PAHs in the soils around thermal power plants A and B are 7436 μg/kg and 8975 μg/kg, respectively indicating heavily pollution. The comprehensive carcinogenic risk of PAHs in thermal power plants A and B ranged from 0.26 × 10 −6 to 4.16 × 10 −6 . Forty percent of the sampling sites exceeded the acceptable risk level (10 −6 ), which is a potential carcinogenic risk to the workers. Among the seven kinds of carcinogens, Bap (39.91%) and DBA (36.10%) had the highest carcinogenic risk. Oral ingestion (57.22%) and skin contact (42.49%) were the major exposure pathways that could be blocked by wearing masks, gloves, and protective clothing. The control values for oral ingestion (0.32717 mg/kg) of DBA and Bap with the highest contribution rate of the carcinogenic risk and the lowest control value were selected as reference safety thresholds for PAHs in thermal power plants.